Cryoprotectant Effect on Erythrocyte Resistance to Detergents Under Band 3 Protein Aggregate State Modification - Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2007)
The erythrocyte hemolysis under the effect of ionic (CTAB, SDS) and non-ionic (Tween 20, Triton X-100) detergents in the presence of cryoprotectants (sucrose, dextran, PEG-1500) and band 3 protein aggregate state modifier (DIDS) was investigated. Cryoprotectants were shown as significantly decreasing erythrocyte sensitivity to CTAB and SDS effect. Protective effect of cryoprotectants against CTAB hemolysis is neutralised by DIDS presence in the medium. However when using Tween 20 DIDS manifests a blocking effect on erythrocyte lysis independently on medium composition. Erythrocyte hemolysis under triton X-100 effect was established as blocked by PEO-1500 but not sucrose, with no influence of DIDS presence in the medium on hemolysis extent. If comparing the Tween 20 and Triton X-100 effects, a protective effect of sucrose may be assumed as limited by its modifying effect on protein membrane components. The analysis of the results obtained enables the concluding about a stabilising effect of cryoprotectants on band 3 protein tetrameric forms.